PENINJAUAN KEMBALI KEDUA DALAM PERKARA PIDANA BERDASARKAN SURAT EDARAN MAHKAMAH AGUNG NOMOR 7 TAHUN 2014: Second Review In Criminal Cases Based On Supreme Court Circular Letter Number 7 Of 2014 - Julian Daniel; Setiyono (Faculty of Law, Universitas Trisakti, 2024)
The right of review is the right of the perpetrator, in contrast to ordinary legal remedies whose application is enshrined in Article 268 paragraph (3) of the Criminal Code. However, in SEMA Number 7 of 2014, a review can be submitted on the grounds that there is a conflict between the decisions. Through Decision 467 Pk/Pid.Sus/2021, the panel of judges decided that the application was unacceptable. From the description above, the author intends to analyze two main issues to be examined, namely whether the decision is in accordance with the Criminal Procedure Code, and whether the reason for the decision is not acceptable to the application. In this paper, the author conducts a descriptive analysis method. Based on the discussion presented in this paper, it is concluded that the decision is not in line with Article 79 of Law Number 14 of 1985 concerning the Supreme Court, using the reason that there is no contradiction submitted as evidences as required in SEMA Number 7 of 2014